The Welfare Economics of Reference Dependence - Daniel Reck; Arthur Seibold (Center for Economic Studies and ifo Institute (CESifo), 2022)
Empirical evidence suggests that individuals often evaluate options relative to a reference point, especially seeking to avoid losses. In this paper, we provide the first welfare analysis under reference-dependent preferences. We decompose the welfare impact of changes in reference points and prices into direct and behavioral effects, and describe how these effects depend on whether reference dependence reflects a bias or a normative preference. In a simple model of loss aversion grounded in common empirical findings, we find that lowering reference points robustly improves welfare, while the welfare effect of a price change depends critically on normative judgments. We also derive sufficient statistics characterizations of the welfare effects of changing reference points and prices. We illustrate these theoretical findings with an empirical application to reference dependence exhibited in German workers' retirement decisions. Both simulation and sufficient statistics results suggest positive welfare effects of increasing the Normal Retirement Age, but ambiguous effects of financial incentives to postpone retirement. Finally, we study how adopting alternative models of reference dependent preferences modifies key welfare effects.
Keywords: D91; D60; H55; J26; 330; reference-dependent preferences; loss aversion; welfare; pension reform